SURG-35. INTRACRANIAL MYXOID MESENCHYMAL TUMOR WITH EWSR1-ATF1 GENE FUSION. (9th November 2020) - Ward, Benjamin; Wang, Christopher; Macaulay, Rob; Liu, James
Abstract: Intracranial myxoid mesenchymal tumors (IMMT) carrying an EWSR1-CREB gene family fusion are extremely rare and have only been identified in ten relatively recent reported cases. There is some question as to whether this is a novel entity, or a myxoid variant of angiomatoid fibrous histiocytoma (AFH), given certain histopathological similarities. Despite these similarities, the increasing number of cases reported appear to demonstrate clear histological differences that indicate IMMTs are a distinct and novel entity. Previous reports have focused on histological analysis but have lacked detailed long-term clinical follow-up and recommendations regarding treatment approach. In this case, we describe a 48-year-old female who presented with a left intraventricular mass that was identified histologically as an IMMT with an EWSR1-ATF1 gene fusion. Following initial resection, the tumor demonstrated local recurrence. Repeat resection was performed followed by immediate demonstration of local, as well as distant, tumor recurrence. Subsequent histological analysis of the tumor demonstrated a myxoid mesenchymal tumor clearly distinct from AFH. Fractionated stereotactic radiation therapy was administered following the second resection and tumor control was achieved at 1 year. This case is particularly remarkable as it is only the second reported IMMT case to occur in a middle-aged adult, with all other cases occurring in children or young adults. The two middle-aged adult cases share striking similarities in clinical presentation, including a history of breast cancer. Our findings indicate that an intracranial myxoid mesenchymal tumor is a novel and rare entity that may demonstrate rapid local and distant recurrence. Given the aggressive recurrence seen with the presented case, we recommend the treatment plan to be surgical resection followed by adjuvant radiation therapy to maintain tumor control.